Associations between polypharmacy and potentially inappropriate medications with risk of falls among the elderly in Saudi Arabia - Khalid S. AlHarkan; Safaa Alsousi; Mujtaba AlMishqab; Majd Alawami; Jaffar Almearaj; Hassan Alhashim; Hassan Alamrad; Layla M. Alghamdi; Abdulelah Almansour; Reem S. AlOmar (BMC Geriatrics, 2023)
Abstract Background Falls are dangerous to the health of older adults and can impact their functional status leading to frailty. The use of potentially inappropriate medications (PIMs) among older adults may lead to adverse health outcomes and increase the risk of falls. Polypharmacy increases the incidence of falls. Beers criteria by the American Geriatric Society is one of the many criteria used to detect PIMs. It assesses the appropriateness of drug prescriptions (i.e., correct dose, duration, and indications) to ensure the safety of these drugs, reducing drug interactions and decreasing the hazards of side effects. This epidemiological study aims to explore the association between polypharmacy and Beers criteria with the risk of falls in the elderly. Method A total of 387 outpatients aged 60 or older were interviewed in person. The patients were recruited from the University Hospital and the Family and Community Medicine Center in Khobar city, Saudi Arabia, between the period of November 2021 to March 2022. All patients were able to walk independently. The survey began by collecting patients’ demographics, gathering medication history, and asking three key questions to detect the risk of falls which was developed by the Center of Disease Control (CDC). Polypharmacy (defined as concurrent use of five or more medications) and PIMs (defined as use of one or more medications in the Beers list) were examined against risk of falls in the elderly. Multiple logistic regression analyses were used to estimate adjusted Odds Ratios (ORs). Result A total of 387 patients participated in the study; 62% were male, and most participants belonged to the 60 < 65 years age category (47.80%). Among all patients, 55% had a high risk of falling, and 21% of patients had fell during the past year. Polypharmacy applied to 50.90% of all patients, while Beers criteria positive group applied to 51.42%. Risk of falls and prior falls were associated with polypharmacy both before and after adjustment. Conclusion The results showed a significant association between risk of falls with polypharmacy and PIMs, and more than half of our study population had a high risk of falls. Of those at a higher risk, one out of five had indeed experienced a fall in the last 12 months. Higher rates of falls were associated with older aged patients, lower educational levels, female gender, and cardiovascular medications.